A novel bioreactor for combined magnetic resonance spectroscopy and optical imaging of metabolism in 3D cell cultures. Issue 5 (16th January 2019) - Cox, Benjamin L.; Erickson‐Bhatt, Sarah; Szulczewski, Joseph M.; Squirrell, Jayne M.; Ludwig, Kai D.; Macdonald, Erin B.; Swader, Robert; Ponik, Suzanne M.; Eliceiri, Kevin W.; Fain, Sean B.
Abstract : Purpose: Fluorescence lifetime imaging microscopy (FLIM) of endogenous fluorescent metabolites permits the measurement of cellular metabolism in cell, tissue and animal models. In parallel, magnetic resonance spectroscopy (MRS) of dynamic nuclear (hyper)polarized (DNP) 13 C‐pyruvate enables measurement of metabolism at larger in vivo scales. Presented here are the design and initial application of a bioreactor that connects these 2 metabolic imaging modalities in vitro, using 3D cell cultures. Methods: The model fitting for FLIM data analysis and the theory behind a model for the diffusion of pyruvate into a collagen gel are detailed. The device is MRI‐compatible, including an optical window, a temperature control system and an injection port for the introduction of contrast agents. Three‐dimensional printing, computer numerical control machining and laser cutting were used to fabricate custom parts. Results: Performance of the bioreactor is demonstrated for 4 T1 murine breast cancer cells under glucose deprivation. Mean nicotinamide adenine dinucleotide (NADH) fluorescence lifetimes were 10% longer and hyperpolarized 13 C lactate:pyruvate (Lac:Pyr) ratios were 60% lower for glucose‐deprived 4 T1 cells compared to 4 T1 cells in normal medium. Looking at the individual components of the NADH fluorescent lifetime, τ1 (free NADH) showed no significant change, while τ2 (bound NADH) showed a significant increase, suggesting that the increase in mean lifetime was due to a change in bound NADH. Conclusion: A novel bioreactor that is compatible with, and can exploit the benefits of, both FLIM and 13 C MRS in 3D cell cultures for studies of cell metabolism has been designed and applied.